Brethren and Separation - Gribben, Crawford 1974- (2021)
John Nelson Darby, one of the most influential Brethren theologians, argued that "separation from evil" was "God’s principle of unity," and his claim defined the worldwide growth of the Brethren movement as it expanded from its origins among the Anglo-Irish elite in the 1820s. As might be expected, the doctrine of separation has been one of the most defining themes in the movement's history, and one of its most controversial features, explaining the relationship between different kinds of Brethren communities, and in many cases policing their links to the wider world. This article describes the evolution of the doctrine of separation among Brethren, and the competing beliefs and behaviours to which it has led, in both Open and Exclusive communities. The article will show how, more recently, changes within these communities have led some Open Brethren to adopt a more stringent doctrine of separation than that maintained by many Exclusive Brethren.
Keywords: Brethren; Separation; John Nelson Darby; Exclusive Brethren; Open Brethren